Imagrability studies : Kuantan Town Centre as a place for people / Sharifah Madznah Syed Mohamed - Syed Mohamed, Sharifah Madznah (Faculty of Architecture, Planning and Surveying, 1990)
Kuantan town lies on the east coast of peninsular Malaysia. It is 2S4 km from Kuala Lumpur. The town centre covers an area of 1 sq. mile (560 acres) and is located by the side of Kuantan river. Several main roads radi ated out off the town centre: Jalan Besar, Jalan Telok Sisek, Jalan Beserah, Jalan Mahkota, Jalan Bukit Ubi, Jalan Weng Ah Jang etc. Besides housing the main government building, the town centre is also the centre for banking and commercial buildings. The townpark and several other green spaces an esplanade which straddles along the Kuantan River